2007
DOI: 10.1097/mpg.0b013e31803e1706
|View full text |Cite
|
Sign up to set email alerts
|

Infant Feeding Patterns in the First 6 Months: An Assessment in Full‐term Infants

Abstract: The most common reason for switching a formula was concern regarding common infantile symptoms or behavior patterns perceived by parents to be related to formula intolerance. The decision to switch formula was usually made by the parents without consulting a health professional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
50
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 22 publications
1
50
0
5
Order By: Relevance
“…An Israeli study undertaken in four maternal and child health care centres between 2002 and 2003 found that 47% of infants experienced a formula change in the first 6 months of life. Most of the formula changes were to another cow’s milk based formula (not defined) and, on average, the first change occurred at 3 months [8]. The EDEN (Étude des Déterminants pré et postnatals du développement et de la santé de l’Enfant) mother-child cohort reported on the effect of the predominant choice of infant formula in the first 4 months of life on infant growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An Israeli study undertaken in four maternal and child health care centres between 2002 and 2003 found that 47% of infants experienced a formula change in the first 6 months of life. Most of the formula changes were to another cow’s milk based formula (not defined) and, on average, the first change occurred at 3 months [8]. The EDEN (Étude des Déterminants pré et postnatals du développement et de la santé de l’Enfant) mother-child cohort reported on the effect of the predominant choice of infant formula in the first 4 months of life on infant growth.…”
Section: Discussionmentioning
confidence: 99%
“…The World Health Organization (WHO) recommend that infant feeding practices are regularly monitored [7] but the literature on type of infant formula practices, in comparison to breastfeeding practices, is scant [813]. To our knowledge only one study [13] reported the use of standard whey-based infant formula at 6 weeks postpartum but did not examine the use of standard whey-based infant formula throughout the first year of life.…”
Section: Introductionmentioning
confidence: 99%
“…Infants who are exclusively formula-fed often receive just one type of formula, which limits their exposure to varied flavor experiences [49] . Despite the lack of flavor variety, different types and brands of formulas vary in their characteristic flavor profile, due to differences in their composition and processing [50] .…”
Section: Formulamentioning
confidence: 99%
“…Although the types of flavors that breastfed infants experience before their first taste of solid foods reflect the culinary practices of their mothers, which varies from infant to infant[60,87], formula-fed infants are usually exposed to constant flavors after birth and prior to weaning, since most formula-fed infants experience a single type of formula[90]. The absence of a robust experimental paradigm, like that employed for other sensory systems (e.g., vision, audition/language) and other animals, has inhibited progress in understanding whether human flavor programming exhibits age-related changes in functional plasticity, commonly referred to as sensitive periods.…”
Section: Sensitive Period For Flavor Learningmentioning
confidence: 99%